Soliton collision management in a microring resonator system - Chat Teeka; Panuwat Chaiyachet; Preecha P. Yupapin (My University, 2009)
We present the interesting system that can be used to solve the problem of signal collision, especially, a soliton pulse in the propagation media. A system consists of a micro ring resonator system incorporating an add/drop filter, whereas the large bandwidth signals can be generated, stored and regenerated within the system. By using the appropriate parameters relating to the practical device such as micro ring radii, coupling coefficients, linear and nonlinear refractive index, we found that the obtained multisolitons can be benefit the dense wavelength division multiplexing application, whereas the different center wavelengths of the soliton bands can be obtained via the add/drop filter without the collision, which can be used to increase the communication channel capacity in communication network. The best of free spectrum range (FSR) and spectral width of the results obtained is 14 nm and 100 pm, respectively, which allows the increasing in channel capacity due to the enough propagation spacing from the collision.
Keywords: Free spectral range; Center frequency; Photonic and Optical Devices